Metallic lithium negative electrode, method for preparing the same, and metallic lithium battery
Patent Information
- Application Number
- CN202510440850.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0013]针对现有技术中存在三维骨架材料与金属锂之间的结合力较弱、无法诱导金属锂向内部沉积、缺乏适应金属锂体积变化的弹性结构等问题,本发明提供了一种新型金属锂负极及其制备方法和金属锂电池
[0057] 1. Lithophilic three-dimensional graphene materials have a large specific surface area, which can support and anchor a large number of lithium-loving sites. These lithium-loving sites can undergo in-situ alloying with the lithium-containing core, firmly connecting the inner cocoon and the lithium-containing core, enhancing the bonding force between the framework and metallic lithium, and facilitating the induction of metallic lithium deposition into the interior to form a stable solid electrolyte membrane.
Smart Images

Figure CN122930853A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium battery technology, specifically to a lithium metal anode, its preparation method, and a lithium metal battery. Background Technology
[0002] Lithium metal is considered an ideal anode material for next-generation high-energy-density batteries due to its extremely high theoretical specific capacity (3860 mAh / g) and the lowest redox potential (-3.04 V vs standard hydrogen electrode). However, lithium metal suffers from serious defects during charge-discharge cycling, such as a large volume expansion effect, a high susceptibility to lithium dendrite formation, and decreased coulombic efficiency. These defects not only affect the cycle life of the battery but may also pose safety hazards, thus limiting the commercial application of lithium metal.
[0003] Currently, constructing three-dimensional framework structures is considered an effective way to solve the problems of lithium metal anodes. A three-dimensional framework can provide sufficient space for lithium metal dendrite growth and volume expansion, while simultaneously reducing local current density, suppressing electrode surface polarization, and hindering lithium dendrite growth. However, existing three-dimensional framework materials have poor wettability with lithium metal, causing lithium metal to tend to deposit on the framework surface, which is not conducive to the formation of a stable solid electrolyte film and cannot effectively mitigate the volume changes of lithium metal during charging and discharging.
[0004] Several invention patents have been filed to address the issues of improving the cycle performance of lithium metal anodes and suppressing lithium dendrite growth. For example:
[0005] Patent CN117438536A discloses a composite lithium metal anode, comprising an active material layer containing an ellipsoidal lithium-carbon material. The lithium-carbon material has a cocoon structure, including a cocoon formed of structural carbon material and one or more lithium metal cores contained within the cocoon. This structure provides sufficient space for lithium metal dendrite growth and volume expansion, which is beneficial for forming a stable solid electrolyte membrane, resulting in a longer cycle life for the anode. However, this patent still faces challenges in optimizing the ellipsoidal size and proportion, as well as the cocoon thickness and porosity, to further improve energy density and cycle performance.
[0006] Patent CN117995991A discloses a lithium metal composite anode, comprising a current collector, a lithiophilic layer, and a lithium metal layer. The lithiophilic layer includes micro / nano lithiophilic particles with a network-structured outer shell on the particle surface. This lithiophilic layer can control the preferential deposition of lithium metal on the current collector surface, effectively suppressing the growth of lithium dendrites on the anode surface. The network structure of the outer shell can improve the bonding force between the lithiophilic layer, the lithium metal layer, and the current collector, significantly improving the cycle performance and lifespan of the lithium metal composite anode. However, this patent still has the problem of further optimizing the lithiophilic layer preparation process to improve performance stability and reliability.
[0007] The existing technology has the following drawbacks:
[0008] 1. Existing three-dimensional framework materials have poor wettability with metallic lithium, and metallic lithium tends to deposit on the surface of the framework, which is not conducive to the formation of a stable solid electrolyte film and cannot effectively alleviate the volume change of metallic lithium during charging and discharging.
[0009] 2. The framework structure size and proportion, as well as parameters such as cocoon thickness and porosity of existing lithium metal composite anode materials need further optimization to improve energy density and cycle performance.
[0010] 3. The existing lithium-metal composite anode material preparation process for the lithium-affinity layer needs further optimization to improve performance stability and reliability.
[0011] 4. The existing lithium metal composite anode materials have a weak bonding force between the framework structure and lithium metal, which cannot effectively induce lithium metal to deposit inward.
[0012] 5. The existing framework structure of lithium metal composite anode materials lacks a spring-like function and cannot adapt to the volume changes of lithium metal during charging and discharging. Summary of the Invention
[0013] To address the problems in existing technologies, such as weak bonding between three-dimensional framework materials and lithium metal, inability to induce lithium metal deposition inward, and lack of elastic structures to adapt to changes in the volume of lithium metal, this invention provides a novel lithium metal anode, its preparation method, and a lithium metal battery.
[0014] In a first aspect, the present invention provides a lithium metal anode, the lithium metal anode comprising a lithium metal composite material, the lithium metal composite material comprising a lithium-containing core and a bilayer cocoon encapsulating the lithium-containing core, the bilayer cocoon comprising an inner cocoon of a lithiophilic three-dimensional graphene material and an outer cocoon of a one-dimensional nanocarbon material, the lithiophilic three-dimensional graphene material having a multi-level pore structure (simultaneously including micropores, mesopores and macropores), the lithiophilic sites being located inside or on the surface of the multi-level pore structure.
[0015] In this invention, a novel lithium metal anode is constructed using a lithium metal composite material with a specific structure, allowing for simultaneous control of its bulk structure, thickness, and areal capacity. The anode bulk phase comprises a bilayer cocoon, which acts like a spring, adapting to the volume changes of lithium metal during charging and discharging. Simultaneously, the bilayer cocoon possesses a large specific surface area and porosity, resulting in a rich pore structure that provides multiple channels for lithium-ion transport, homogenizes current distribution, and effectively suppresses the generation and growth of lithium dendrites. This gives the lithium metal anode excellent cycle performance and rate capability, surpassing the performance of anodes composed of a single one-dimensional nano-carbon material forming the cocoon.
[0016] Optionally, the thickness of the negative electrode is 1-100 μm, preferably 5-50 μm.
[0017] Optionally, the specific capacity of the negative electrode is above 1200 mAh / g, preferably 1500-3500 mAh / g.
[0018] Optionally, the lithium-containing core comprises metallic lithium and / or a lithium alloy, wherein the alloying element in the lithium alloy comprises at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, or zinc.
[0019] Optionally, the lithium alloy contains more than 50% metallic lithium, preferably 60-95%.
[0020] Optionally, the average particle size of the lithium-containing core is 1-100 μm, preferably 5-50 μm.
[0021] Optionally, the one-dimensional carbon nanomaterial includes at least one of carbon nanofibers, single-walled carbon nanotubes, or multi-walled carbon nanotubes.
[0022] Optionally, the outer diameter of the one-dimensional carbon nanomaterial is ≤300nm, preferably 1-20nm, and more preferably 1-10nm.
[0023] Optionally, the length of the one-dimensional carbon nanomaterial is 0.5 μm to 500 μm, preferably 1-100 μm, and more preferably 5-50 μm.
[0024] Optionally, the BET specific surface area of the lithiophilic three-dimensional graphene material is 1-50 m² / g, preferably 5-20 m² / g.
[0025] Optionally, the size of the three-dimensional graphene material is smaller than the size of the lithium-containing core, preferably 0.5-20 micrometers, and more preferably 1-10 micrometers.
[0026] Optionally, the lithiophilic three-dimensional graphene material comprises at least one lithiophilic element selected from tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, and zinc.
[0027] Optionally, the mass ratio of the lithiophilic element to the three-dimensional graphene in the lithiophilic three-dimensional graphene material is 1:(1-50), preferably 1:(5-20).
[0028] Optionally, in the lithiophilic three-dimensional graphene material, the lithiophilicity of the lithiophilic element is weaker than that of the lithium-containing core.
[0029] Optionally, the mass ratio of the one-dimensional carbon nanomaterial to the lithiophilic three-dimensional graphene material is 1:(0.5-50), preferably 1:(1-20).
[0030] Optionally, the mass ratio of the double-layered cocoon to the lithium-containing core is 1:(0.1-100), preferably 1:(0.5-50).
[0031] Optionally, the negative electrode further includes a current collector, and at least one side of the current collector is provided with a lithium metal composite material layer.
[0032] Optionally, the current collector includes at least one of double-sided copper foil, textured copper foil, single-sided copper foil, carbon-coated copper foil, nickel foil, stainless steel foil, polymer fiber conductive cloth, carbon cloth, or carbon nanotube paper.
[0033] In a second aspect, the present invention also provides a method for preparing a lithium metal anode as described in the first aspect above, the method comprising the following steps:
[0034] Step 1: Mix the lithiophilic three-dimensional graphene material, the lithium-containing core, and the first organic solvent, and then set the inner cocoon on the surface of the lithium-containing core by high-speed winding or spray drying to obtain the lithiophilic composite material.
[0035] Step 2: Mix the one-dimensional carbon nanomaterial, the second organic solvent, and the lithiophilic composite material from Step 1, and freeze-dry or spray-dry to set an outer cocoon on the surface of the lithiophilic composite material to obtain a lithium metal composite material.
[0036] Step 3: Mold the lithium metal composite material using a dry or wet process to obtain a lithium metal anode.
[0037] Optionally, the organic solvent in steps 1 and 2 includes at least one of the following: liquid alkanes with 5-20 carbon atoms, liquid cycloalkanes with 5-20 carbon atoms, benzene, toluene, xylene, solvent oil D20, solvent oil D40, solvent oil D60, solvent oil D80, silicone oil, light paraffin, N-methylpyrrolidone, or N,N-dimethylformamide.
[0038] Optionally, step 1 further includes: heat-treating the lithiophilic composite material.
[0039] Optionally, the heat treatment temperature is less than or equal to the melting point of the lithium-containing core.
[0040] Optionally, the heat treatment time is 0.5-5 hours, preferably 1-3 hours.
[0041] Optionally, the preparation method of the lithiophilic three-dimensional graphene material in step 1 includes at least one of the following: hydrothermal method, solvothermal method, vapor deposition method, atomic layer deposition method, or vacuum evaporation method.
[0042] For example, the conditions for preparing lithiophilic three-dimensional graphene materials using the solvothermal method are as follows: Three-dimensional graphene and lithiophilic materials (such as silver nitrate, silver acetate, silver oxalate, etc.) are dispersed in an organic solvent such as ethanol, transferred to a stainless steel reactor, and reacted at 200-230℃ for 12-24 hours to obtain lithiophilic three-dimensional graphene materials. The hydrothermal method operates similarly to the solvothermal method, the difference being that the solvent contains water.
[0043] Conditions for preparing lithiophilic three-dimensional graphene materials by vacuum evaporation: using elemental lithiophilic material as the evaporation source and three-dimensional graphene material as the substrate, the content (mass percentage) of elemental lithiophilic material in three-dimensional graphene is controlled under vacuum by controlling the heating temperature, deposition rate and time.
[0044] Optionally, the high-speed winding speed in step 1 is above 3000 rpm, preferably 5000-15000 rpm.
[0045] Optionally, the high-speed winding time is 5-90 minutes, preferably 10-60 minutes.
[0046] Optionally, the inlet air temperature for spray drying in step 1 is 180~240℃, for example, it can be 180℃, 185℃, 190℃, 200℃, 210℃, 220℃, 230℃ or 240℃, etc., including but not limited to the values listed above, preferably 200~220℃.
[0047] Optionally, the outlet air temperature of the spray dryer is 80~120℃, for example, it can be 80℃, 85℃, 90℃, 100℃, 110℃ or 120℃, etc., including but not limited to the values listed above, preferably 100~110℃.
[0048] Optionally, the atomization pressure of the spray drying is 0.1~0.5 MPa, for example, it can be 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa or 0.5 MPa, etc., including but not limited to the values listed above, and preferably 0.2~0.4 MPa.
[0049] Optionally, the mixing in step 2 includes the following operations: mixing the one-dimensional carbon nanomaterial and the organic solvent once, and then adding the lithiophilic composite material for a second mixing.
[0050] Optionally, the mixing in step 2 may employ at least one of high-speed dispersion, high-pressure homogenization, or high-pressure turbulence.
[0051] Optionally, the pressure of the high-pressure homogenization and high-pressure turbulence is independently 500-2000 bar, preferably 600-1500 bar.
[0052] Optionally, the forming method in step 3 includes at least one of roll pressing and / or flat pressing, binder fiberization, electrostatic spraying, or coating.
[0053] Optionally, the adhesive used in the adhesive fiberization method includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, or styrene-butadiene rubber.
[0054] Optionally, in the binder fiberization method or electrostatic spraying method, the mass ratio of the binder to the lithium metal composite material is independently (1-20):(80-99), preferably (3-10):(90-97). "Independently" means that the mass ratios in the binder fiberization method or electrostatic spraying method do not affect each other and can be designed separately according to actual needs.
[0055] Thirdly, the present invention also provides a lithium metal battery, the lithium metal battery comprising a negative electrode as described in the first aspect above.
[0056] Compared with the prior art, the present invention has at least the following beneficial effects:
[0057] 1. Lithophilic three-dimensional graphene materials have a large specific surface area, which can support and anchor a large number of lithium-loving sites. These lithium-loving sites can undergo in-situ alloying with the lithium-containing core, firmly connecting the inner cocoon and the lithium-containing core, enhancing the bonding force between the framework and metallic lithium, and facilitating the induction of metallic lithium deposition into the interior to form a stable solid electrolyte membrane.
[0058] 2. The double-layered cocoon acts like a spring, adapting to the volume changes of lithium metal during charging and discharging, mitigating the volume expansion effect, and improving the cycle stability of the lithium metal anode.
[0059] 3. The double-layered cocoon has a large specific surface area and porosity, forming a rich pore structure, providing multiple channels for lithium-ion transport, homogenizing current distribution, effectively suppressing the generation and growth of lithium dendrites, and improving cycle life and rate performance.
[0060] 4. The preparation method of lithium metal composite materials is simple. Through high-speed winding, spray drying, freeze drying and other processes, the double cocoon can be uniformly coated on the lithium core surface, which improves the performance stability and reliability of the material. Attached Figure Description
[0061] Figure 1 The cyclic test curves are for Examples 2, 5, and 7;
[0062] Figure 2 The cyclic test curves are for Examples 2 and 8-10;
[0063] Figure 3The cyclic test curves are for Example 2 and Comparative Examples 3-4. Detailed Implementation
[0064] To facilitate understanding of this application, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of this application.
[0065] Example 1
[0066] This embodiment provides a lithium metal anode, which includes a lithium metal composite material. The composite material includes lithium metal powder with a particle size of 50 μm and a double-layer cocoon disposed on its surface. The inner cocoon includes a three-dimensional graphene material containing silver particles. The inner cocoon and the lithium-containing core are connected by an in-situ generated lithium-silver alloy. The outer cocoon is a double-walled carbon nanotube, which is connected to the inner cocoon by interweaving and entanglement.
[0067] The method for preparing the negative electrode includes the following steps:
[0068] (1) Dissolve 0.32g of silver nitrate in ethanol, and add 10g of three-dimensional graphene (purchased from Chihe New Materials Technology Nanjing Co., Ltd., with a specific surface area of 400-800m²). 2 / g, with 3-7 layers, pore size distribution of 30-80 nanometers, and average particle size of 5 micrometers) were ultrasonically treated and mixed evenly, and then transferred to a stainless steel reactor and reacted at 200℃ for 18 hours. The mass ratio of silver was 2%, and silver-containing three-dimensional graphene material was obtained.
[0069] (2) Mix 5g of silver-containing three-dimensional graphene material (5 micrometers, with a silver mass ratio of 2%), 0.51g of lithium metal powder and n-hexane, disperse at high speed at 8000rpm for 60min, set the silver-containing three-dimensional graphene material on the surface of lithium metal powder, and vacuum dry at 90℃ to obtain a lithium-loving composite material.
[0070] (3) Mix 0.1g of double-walled carbon nanotubes (purchased from Beijing Deco Island Gold Technology Co., Ltd., with an outer diameter of 2-4nm and a length of 5-15μm), dimethyl ether and the lithium-loving composite material in step (1), keep at 12000rpm for 20min, set the outer cocoon formed by double-walled carbon nanotubes on the surface of the lithium-loving composite material, freeze dry, and obtain the lithium metal composite material.
[0071] (4) The lithium metal composite material is rolled and formed under a pressure of 20 kg to prepare a negative electrode with a thickness of 100 micrometers.
[0072] Example 2
[0073] This embodiment provides a lithium metal anode, which includes a lithium metal composite material. The composite material includes lithium silver powder with a particle size of 50 μm and a double cocoon disposed on its surface. The inner cocoon includes a three-dimensional graphene material containing tin particles. The inner cocoon and the lithium-containing core are connected by an in-situ generated lithium-tin alloy. The outer cocoon is a single-walled carbon nanotube, which is connected to the inner cocoon by interweaving and entanglement.
[0074] The method for preparing the negative electrode includes the following steps:
[0075] (1) Using elemental tin as the evaporation source and 10g of three-dimensional graphene (purchased from Shanghai Hydrogen Field New Material Technology Co., Ltd., with a specific surface area of 500m2 / g, 2-4 layers, pore size distribution of 500-1000 nanometers, and average particle size of 1 micrometer) as the substrate, tin was deposited onto the surface and interior of the multi-level pore structure in the three-dimensional graphene by vacuum evaporation, and the mass ratio of tin was controlled to be 50% to obtain tin-containing three-dimensional graphene material.
[0076] (2) Mix 0.5g of tin-containing three-dimensional graphene material (1 micrometer, tin mass percentage of 50%), 150g of lithium silver alloy powder (silver mass percentage of 5%) and solvent oil D40, disperse at high speed at 10000rpm for 45min, set tin-containing three-dimensional graphene material on the surface of lithium silver alloy powder, and vacuum dry at 120℃ to obtain lithium-loving composite material;
[0077] (3) 1g of single-walled carbon nanotubes (purchased from Shandong Carbon Seeking New Materials Co., Ltd., radius 1.4±0.5nm, length>100 micrometers), N-methylpyrrolidone and the lithiophilic composite material in step (1) were mixed at 1000 bar and 6000 prm for 90 min. After spray drying, an outer cocoon formed by double-walled carbon nanotubes was set on the surface of the lithiophilic composite material. The inlet air temperature was 220℃, the outlet air temperature was 90℃, and the atomization pressure was 0.5 MPa to obtain the lithium metal composite material.
[0078] (4) The lithium metal composite material is rolled and formed under a pressure of 30 kg to prepare a negative electrode with a thickness of 50 micrometers.
[0079] Example 3
[0080] Compared with Example 2, the only difference is that the mass percentage of tin in the tin-containing three-dimensional graphene material in step (2) is replaced with 16.7%, at which point the mass ratio of tin to three-dimensional graphene is about 1:5, and the other conditions remain unchanged.
[0081] Example 4
[0082] Compared with Example 2, the only difference is that the mass percentage of tin in the tin-containing three-dimensional graphene material in step (2) is replaced with 47.6%, at which point the mass ratio of tin to three-dimensional graphene is about 1:20, and the other conditions remain unchanged.
[0083] Example 5
[0084] Compared with Example 2, the only difference is that the mass of the tin-containing three-dimensional graphene material in step (2) is replaced with 1g, while the other conditions remain unchanged.
[0085] Example 6
[0086] Compared with Example 2, the only difference is that the mass of the tin-containing three-dimensional graphene material in step (2) is replaced with 20g, while the other conditions remain unchanged.
[0087] Example 7
[0088] Compared with Example 2, the only difference is that the mass of lithium silver powder in step (2) is replaced with 0.75g, while the other conditions remain unchanged.
[0089] Example 8
[0090] Compared with Example 2, the only difference is that the mass of lithium silver powder in step (2) is replaced with 75g, while the other conditions remain unchanged.
[0091] Example 9
[0092] Compared with Example 2, the only difference is that the lithium silver powder in step (2) is replaced with lithium magnesium silver powder, with magnesium accounting for 5% of the mass and silver accounting for 5% of the mass, while the other conditions remain unchanged.
[0093] Example 10
[0094] Compared with Example 2, the only difference is that the lithium silver powder in step (2) is replaced with lithium boron indium powder, the mass percentage of boron is 1% and the mass percentage of indium is 4%, and the other conditions remain unchanged.
[0095] Example 11
[0096] Compared with Example 2, the only difference is that the mass of the single-walled carbon nanotubes in step (3) is replaced with 0.5g, while all other conditions remain unchanged.
[0097] Example 12
[0098] Compared with Example 2, the only difference is that the mass of the single-walled carbon nanotubes in step (3) is replaced with 0.025g, while all other conditions remain unchanged.
[0099] Comparative Example 1
[0100] Compared with Example 2, the only difference is that the composite material in the negative electrode includes cocoons formed by lithium silver particles and single-walled carbon nanotubes, but does not include cocoons formed by tin-containing three-dimensional graphene materials.
[0101] Comparative Example 2
[0102] Compared with Example 2, the only difference is that the composite material in the negative electrode includes cocoons formed by lithium silver particles and tin-containing three-dimensional graphene materials, but does not include cocoons formed by single-walled carbon nanotubes.
[0103] Comparative Example 3
[0104] Compared to Example 2, the only difference is that the material in the negative electrode includes lithium silver particles, but does not include the bilayer cocoon of single-walled carbon nanotubes and tin-containing three-dimensional graphene material.
[0105] Comparative Example 4
[0106] Compared with Example 2, the only difference is that the composite material in the negative electrode includes lithium silver particles, the surface of which has a single-layer cocoon, which is composed of single-walled carbon nanotubes and tin-containing three-dimensional graphene material, and does not form the double-layer cocoon as in this invention.
[0107] The preparation method includes the following steps: (1) 1g of single-walled carbon nanotubes, 0.5g of tin-containing three-dimensional graphene material (tin mass ratio is 50%), 150g of lithium silver alloy powder (silver mass ratio is 5%) and solvent oil D40 are mixed at 1000 bar and 6000 prm for 90 min. After spray drying, the inlet air temperature is 220℃, the outlet air temperature is 90℃, and the atomization pressure is 0.5 MPa to obtain the composite material.
[0108] Comparative Example 5
[0109] Compared with Example 2, the only difference is that the tin-containing three-dimensional graphene material is replaced with a tin-containing two-dimensional graphene material (the three-dimensional graphene material is replaced with a two-dimensional graphene material (purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., XF021 7440-44-0)), and all other conditions remain the same.
[0110] Performance testing:
[0111] The negative electrodes from Examples 1-12 and Comparative Examples 1-5 were used to assemble 1Ah pouch cells with NCM811 positive electrodes. The electrolyte was an ether-based solution purchased from Shenzhen Kejing Materials Technology Co., Ltd. Cycle performance was tested under 0.5 / 1C conditions, with the cutoff condition being the occurrence of a short circuit or the discharge capacity reaching 80% of the initial discharge capacity.
[0112] Table 1
[0113]
[0114] As can be seen from Table 1:
[0115] (1) Comparing Example 2 and Example 3-4, it can be seen that the number of cycles in Example 3-4 is more than that in Example 2. This is because the mass ratio of tin to three-dimensional graphene in Example 3-4 is more suitable, and the inner cocoon constructed by the tin-containing three-dimensional graphene material is more stable, which significantly improves the cycle performance of the negative electrode.
[0116] (2) Comparing Examples 2 and 5-6, it can be seen that the number of cycles in Examples 5-6 is more than that in Example 2. This is because the mass ratio of the tin-containing three-dimensional graphene material and the single-walled carbon nanotubes in Examples 5-6 is more suitable, and the two work together to make the double-layer cocoon structure stable, and the negative electrode can effectively adapt to the volume change of lithium metal during charging and discharging; combined with Figure 1 It can be seen that the negative electrode in Example 5 exhibits excellent performance and better cycle stability than that in Example 2;
[0117] (3) Comparing Examples 2 and 7-8, it can be seen that the number of cycles in Examples 7-8 is greater than that in Example 2. This is because the mass ratio of lithium silver powder to the double-layer cocoon is more suitable in Examples 7 and 8, resulting in a longer cycle life of the negative electrode; combined with Figure 1 and Figure 2 It can be seen that the cycle stability and cycle life of Examples 7 and 8 are better than those of Example 2;
[0118] (4) Comparing Examples 2 and 9-10, it can be seen that the number of cycles in Examples 9-10 is more than that in Example 2. This is because the lithium core in Examples 9 and 10 is a ternary alloy, and the alloying elements have a better deposition effect on metallic lithium than binary alloys; combined with Figure 3 It can be seen that the cycle stability and cycle life of Examples 9 and 10 are better than those of Example 2;
[0119] (5) Comparing Example 2 and Example 11-12, it can be seen that the number of cycles in Example 2 is more than that in Example 11-12. This is because the mass of single-walled carbon nanotubes in Example 11-12 is less, the outer cocoon formed is thinner, and the adaptability to the volume change of metallic lithium is poor.
[0120] (6) Comparing Example 2 and Comparative Examples 1-5, it can be seen that the number of cycles in Example 2 is more than that in Comparative Examples 1-4. This is because the cocoon composition and structure of the lithium metal material in the negative electrode of Comparative Examples 1-5 are different from those in Example 2, and the stability of the structure and its adaptability to changes in the volume of lithium metal are poor. The overpotential of Comparative Example 5 reaches 1V faster than that in Example 2. This is because of the essential difference between the two-dimensional graphene material in Comparative Example 5 and the three-dimensional graphene material in Example 2: Three-dimensional graphene is a new type of carbon nanomaterial composed of two-dimensional graphene on a macroscopic scale. It can maintain the excellent characteristics of graphene's ultra-large specific surface area and ultra-high conductivity while overcoming the π-π interaction force between graphene sheets, effectively blocking the self-disordered stacking of graphene sheets, and thus achieving the stability of its macroscopic structure. At the same time, three-dimensional graphene material has a multi-level porous structure, which is more conducive to the transport of lithium ions and the regulation of current density. As an inner cocoon, three-dimensional graphene can connect with the outer cocoon better than two-dimensional graphene. Figure 3 It can be seen that although the overpotential in Comparative Example 4 is very low, a short circuit occurs quickly. This is because although three-dimensional graphene material was used in Comparative Example 4, the structure of the present invention was not formed. In Comparative Example 3, dendrites quickly appeared on the negative electrode under the high-rate discharge conditions of 0.5C / 1C, resulting in a short circuit.
[0121] The applicant declares that this application illustrates its detailed structural features through the above embodiments, but this application is not limited to the above detailed structural features, that is, it does not mean that this application must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the components selected in this application, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.
Claims
1. A lithium metal anode, characterized in that, The lithium metal anode includes a lithium metal composite material, which includes a lithium-containing core and a bilayer cocoon encapsulating the lithium-containing core. The bilayer cocoon includes an inner cocoon of lithium-loving three-dimensional graphene material and an outer cocoon of one-dimensional nanocarbon material. The lithium-loving three-dimensional graphene material has a hierarchical porous structure, and the lithium-loving sites are located inside or on the surface of the hierarchical porous structure.
2. The negative electrode according to claim 1, characterized in that, The thickness of the negative electrode is 1-100 μm, preferably 5-50 μm; Preferably, the specific capacity of the negative electrode is above 1200 mAh / g, and more preferably 1500-3500 mAh / g; Preferably, the lithium-containing core comprises metallic lithium and / or a lithium alloy, wherein the alloying element in the lithium alloy comprises at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, or zinc. Preferably, the lithium alloy contains more than 50% metallic lithium, and more preferably 60-95% metallic lithium. Preferably, the average particle size of the lithium-containing core is 1-100 μm, and more preferably 5-50 μm.
3. The negative electrode according to claim 1 or 2, characterized in that, The one-dimensional carbon nanomaterial includes at least one of carbon nanofibers, single-walled carbon nanotubes, or multi-walled carbon nanotubes. Preferably, the outer diameter of the one-dimensional carbon nanomaterial is ≤300nm, more preferably 1-20nm, and even more preferably 1-10nm; Preferably, the length of the one-dimensional carbon nanomaterial is 0.5 μm to 500 μm, more preferably 1-100 μm, and even more preferably 5-50 μm.
4. The negative electrode according to any one of claims 1-3, characterized in that, The BET specific surface area of the affinity-based three-dimensional graphene material is 1-50 m² / g, preferably 5-20 m² / g; Preferably, the size of the three-dimensional graphene material is smaller than the size of the lithium-containing core, preferably 0.5-20 micrometers, and more preferably 1-10 micrometers; Preferably, the lithiophilic three-dimensional graphene material comprises at least one lithiophilic element selected from tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, and zinc; Preferably, the mass ratio of the lithiophilic element to the three-dimensional graphene in the lithiophilic three-dimensional graphene material is 1:(1-50), more preferably 1:(5-20). Preferably, in the lithiophilic three-dimensional graphene material, the lithiophilicity of the lithiophilic element is weaker than that of the lithium-containing core.
5. The composite material according to any one of claims 1-4, characterized in that, The mass ratio of the one-dimensional carbon nanomaterial to the lithiophilic three-dimensional graphene material is 1:(0.5-50), preferably 1:(1-20). Preferably, the mass ratio of the double-layered cocoon to the lithium-containing core is 1:(0.1-100), more preferably 1:(0.5-50).
6. The negative electrode according to any one of claims 1-5, characterized in that, The negative electrode also includes a current collector, and a lithium metal composite material layer is disposed on at least one side of the current collector; Preferably, the current collector includes at least one of double-sided copper foil, textured copper foil, single-sided copper foil, carbon-coated copper foil, nickel foil, stainless steel foil, polymer fiber conductive cloth, carbon cloth, or carbon nanotube paper.
7. A method for preparing a negative electrode as described in any one of claims 1-6, characterized in that, The method includes the following steps: Step 1: Mix the lithiophilic three-dimensional graphene material, the lithium-containing core, and the first organic solvent, and then set the inner cocoon on the surface of the lithium-containing core by high-speed winding or spray drying to obtain the lithiophilic composite material. Step 2: Mix the one-dimensional carbon nanomaterial, the second organic solvent, and the lithiophilic composite material from Step 1, and freeze-dry or spray-dry to set an outer cocoon on the surface of the lithiophilic composite material to obtain a lithium metal composite material. Step 3: Mold the lithium metal composite material using a dry or wet process to obtain a lithium metal anode.
8. The method according to claim 7, characterized in that, The organic solvents in steps 1 and 2 include at least one of the following: liquid alkanes with 5-20 carbon atoms, liquid cycloalkanes with 5-20 carbon atoms, benzene, toluene, xylene, solvent oil D20, solvent oil D40, solvent oil D60, solvent oil D80, silicone oil, light paraffin, N-methylpyrrolidone, or N,N-dimethylformamide. Preferably, step 1 further includes: heat-treating the lithiophilic composite material.
9. The method according to claim 7 or 8, characterized in that, The preparation method of the lithiophilic three-dimensional graphene material in step 2 includes at least one of the following: hydrothermal method, solvothermal method, vapor deposition method, atomic layer deposition method, or vacuum evaporation method.
10. A lithium metal battery, characterized in that, The lithium metal battery includes a negative electrode as described in any one of claims 1-6.